Land use change, fragmentation, and sea level rise create escalating viability concerns for an imperiled salamander - Leyna R. Stemle; David Laabs; Christopher A. Searcy (Ecosphere)
Abstract Many organisms with complex life cycles rely on both terrestrial and aquatic habitats to survive, which increases their susceptibility to habitat fragmentation as they require access to sufficient amounts of both habitat types as well as connectivity between them. Amphibian species are often very susceptible to these anthropogenic disturbances and are declining across the globe. We conducted the first range‐wide geospatial analysis for the federally endangered Santa Cruz long‐toed salamander (SCLTS; Ambystoma macrodactylum croceum) to address the impacts of land use change and habitat fragmentation as barriers to recovery. First, we used data from an extensive drift fence array to determine the mean, 95%, and 99% migration distances of SCLTS. We then used these calculated distances to determine the amount of suitable and accessible upland habitat around all current breeding ponds as well as those being considered as potential release sites. Land use changes (especially urban and agricultural development) have reduced the amount of suitable upland habitat within migration distance of SCLTS breeding ponds by 35.5% across the range. Habitat fragmentation due to roads has further reduced uplands both suitable and accessible to SCLTS by another 11.8%, and sea level rise projected by 2100 reduces it another 16.2%, leaving only 36.5% of potential terrestrial habitat suitable, accessible, and unflooded. This result raises substantial concerns about the long‐term viability of the majority of SCLTS populations. This range‐wide assessment also provides guidance on which breeding populations should be targeted for land use restoration and experimental road crossing structures and which potential breeding sites should be prioritized for release of captive‐bred animals.